If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -8 + 1 = -9 + 2 Combine like terms: -8 + 1 = -7 -7 = -9 + 2 Combine like terms: -9 + 2 = -7 -7 = -7 Add '7' to each side of the equation. -7 + 7 = -7 + 7 Combine like terms: -7 + 7 = 0 0 = -7 + 7 Combine like terms: -7 + 7 = 0 0 = 0 Solving 0 = 0 Couldn't find a variable to solve for. This equation is an identity, all real numbers are solutions.
| 12x+3=93 | | (9r+7)(2r-6)=0 | | 12x+2x=24 | | 3=-8x-8 | | p+30=21 | | V=1.05(2.38x^2+2.38*1.46+1.46x^2)h | | 5x^2-20x+20= | | 3y-6x=24-3x | | 15(E-3)=-10(E+2) | | r(r)+3r=6 | | x^3+3x-14=0 | | 4(7-y)+2y=8 | | x+12=4x+52 | | 7=-3+3x | | =2x^2+2x-12 | | 4x+10y=1 | | 4x+7+6=-5x-23 | | -(8y+1)-(-7y-6)=1 | | =23x^2-22x | | 7x=84x | | 6(4x-9)=3(8x+5) | | 8+6r-7=7r+3-2r | | 8+6r-7r=7r+3-2r | | =(y-5)(y-3) | | A^3b^2= | | 4c^2+24c+30=0 | | =x^3-27 | | 2x+[3x-2(x-2y)-3x]= | | =15a^2+11a+2 | | 9x+6+4x+x-9= | | -3x-(2-x)=-2(2-3x) | | 13(t-4)+8t=7(3t+5)-8 |